Risk factors for repetition of a deliberate self-harm episode within seven days in adolescents and young adults: A population-level record linkage study in Western Australia - Hu, N.; Glauert, R.; Li, Jianghong; Taylor, C. (Sage Publications Ltd., 2016)
Objective: The risk of repetition of deliberate self-harm peaks in the first 7 days after a deliberate self-harm episode. However, thus far no studies have examined the risk factors for repeating deliberate self-harm during this short-term period. We aimed to investigate the effects of socio-demographic factors, self-harm method and mental health factors in adolescents (10-19 years old) and young adults (20-29 years old). Methods: We used data linkage of population-wide administrative records from hospital inpatients and emergency departments to identify all the deliberate self-harm-related episodes that occurred in adolescents and young adults in Western Australia from 2000 to 2011. Logistic regression with generalised estimating equations was used for the analyses. Results: The incidence of repeating deliberate self-harm within the first 7 days after an index episode was 6% (403/6,768) in adolescents and 8% (842/10,198) in young adults. Socio-demographic risk factors included female gender and socioeconomic disadvantage. Compared with non-poisoning, self-poisoning predicted increased risk of having a repeated deliberate self-harm episode in males, but not in females. Borderline personality, impulse-control and substance use disorders diagnosed within one week before and one week after an index deliberate self-harm episode conferred the highest risk, followed by depressive and anxiety disorders. Having a preceding deliberate self-harm episode up to 7 days before an index episode was a strong predictor for the future repetition of a deliberate self-harm episode.Conclusion: Having a repeated deliberate self-harm episode within the first 7 days was related to a wide range of factors present at an index deliberate self-harm episode including socio-demographic characteristics, deliberate self-harm method and co-existing psychiatric conditions. These factors can inform risk assessments tailored to adolescents and young adults respectively to reduce the repetition of deliberate self-harm within a short but critical period, potentially contributing to reduce the repetition of deliberate self-harm in the long term.